2016
DOI: 10.1016/j.psychres.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dysfunctional impulsivity and alexithymia on aggressive behavior of psychiatric patients

Abstract: Current approaches in Dutch mental health care institutions towards inpatients' aggression have focused predominantly on environmental factors, such as training the staff in aggression management. However, personality traits might be an important factor in patients' aggressionas shown by incidents in the wards. This study explores the influence of dysfunctional impulsivity and alexithymia on psychiatric patients' aggressive behavior, through self-reports and through involvement in aggressive incidents. Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…This seems to be because the scale used in this study reflects only direct and active hostility ( 59 ). Given that previous studies have reported a link between hostility and alexithymia ( 28 ), further study needs to identify the dynamics of alexithymia using a tool that can measure passive aggression, which involves the use of implicitly hostile words or behaviors as well as active forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be because the scale used in this study reflects only direct and active hostility ( 59 ). Given that previous studies have reported a link between hostility and alexithymia ( 28 ), further study needs to identify the dynamics of alexithymia using a tool that can measure passive aggression, which involves the use of implicitly hostile words or behaviors as well as active forms.…”
Section: Discussionmentioning
confidence: 99%
“…An equally incoherent picture has emerged from research exploring the relationships of alexithymia with problematic emotional expressions, including impulsivity, aggression, or hostility (27)(28)(29)(30)(31)(32). For example, while gender has been reported as a significant variable influencing impulse control problems such as drinking, gambling, and suicide (33), little is known about whether gender contributes to alexithymia-related externalizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…The city of Cuernavaca was a good place to carry out this study because of the amount of stress generated by traffic within its limits Dorantes-Argandar et al, 2015a, 2015bLima-Aranzaes, Juárez-García, & Arias-Galicia, 2012). This paper provides theoretical insight onto how psychological constructs within individuals themselves have an impact on their driving styles and behaviors, such as was found in other studies (de Schutter et al, 2016;Hahn et al, 2016). It also paves the road towards the conception of a fixed set of driving styles or driver personalities in Mexico, such as Marengo et al(2012)propose in Italy.…”
Section: Discussionmentioning
confidence: 56%
“…A study carried out in psychiatric patients found that personality variables such as alexithymia and impulsivity were consistent predictors of aggressive behavior (de Schutter et al, 2016). This serves as an argument towards characterizing overly aggressive drivers as people in need of psychiatric care, or at least treatment in personality issues.…”
mentioning
confidence: 99%
“…Although we explicitly made use of a non-offending sample in this project, those demonstrating high scores on the Buss-Perry Aggression Questionnaire have been shown to demonstrate forensic-related behaviors, such as emotional reactivity to perceived provocation, poor situational problem-solving, interpersonal aggression, impulsivity, and attempts at relational dominance (Archer & Webb, 2006;de Schutter, Kramer, Franken, Lodewijkx, & Kleinepier, 2016;Tremblay & Ewart, 2005 Crime and Delinquency Measure. We adapted scales used by Chen, Voisin, and Jacobson (2016) and Elliot, Huizinga, and Ageton (1985) to create measures of criminal behavior (nine items; e.g., "Stolen money or taken something that did not belong to you") and…”
Section: Participantsmentioning
confidence: 99%